The Green and the Blue Digital Politics in Philosophical Discussion - Floridi, Luciano (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
How can Europe benefit politically and socially from the possibilities of digitization and overcome its crises, which have plagued it so much in recent times? How can it realize a "human project" and the unity of "green" ecology and "blue" information technology? In this volume, Luciano Floridi presents a synthesis of his theses on how digitalization affects everyday political and social phenomena, and how it is now not so much things as their relations that are gaining importance. With critical contributions by Manfred Broy, Markus Gabriel, Armin Grunwald, Ruth Hagengruber, Alexander Kriebitz, Christoph Lütge, Raphael Max, Catrin Misselhorn, and Malte Rehbein.